Governance Disclosure Practices of Corporate Sector - Gupta, Meenu (Gyan Management Journal, 2015)
The issue of corporate governance continues to receive a high level of attention. Corporate governance is like a blood which fills the veins of corporate disclosure in form of transparency. The recent global events concerning high profile corporate failures have put banks in the debate on the efficiency of corporate governance mechanisms as a means of increasing firm’s performance. This paper makes the comparison regarding corporate disclosure practices in top ten private companies for the year 2003- 04 with 2013-14. It also includes the broad view of corporate governance in India. The study uses secondary sources of data and finds the differences in the ranking of the companies as per highest market capitalization and governance practices followed by them. The results indicate that there has been improvement of disclosure practices in corporate sector over the years